Religion, culture and national community in the 1670s - Claydon, Tony; Corns, Thomas N. (Religion, education, and culture., 2011)
This fascinating collection of essays illustrates the latest thinking on the crucial decade of the 1670s in Britain. In 1660, after eleven years of republican regimes, the royal restoration attempted to set the political, cultural, and religious clock back to the days of the early Stuarts. By the 1670s, however, this restoration settlement was unraveling, challenged by new ideas of religious toleration, popular sovereignty, and diverse nationality. These essays reflect and analyze such tensions and illustrate the surprising routes by which the modern world began to emerge.